(untitled) - Costenbader, Carol W. (North Adams, MA., 2002)
Remember how grandmother's cellar shelves were packed with jars of tomato sauce and stewed tomatoes, pickled beets and cauliflower, and pickles both sweet and dill? Learn how to save a summer day - in batches - from the classic primer, now updated and rejacketed. Use the latest inexpensive, time-saving techniques for drying, freezing, canning, and pickling. Anyone can capture the delicate flavors of fresh foods for year-round enjoyment and create a well-stocked pantry of fruits, vegetables, herbs, meats, flavored vinegars, and seasonings. The Big Book of Preserving the Harvest introduces the basic technique for all preserving methods, with step-by-step illustration, informative charts and tips throughout, and more than 150 recipes for the new or experienced home preserver. Among the step-by-step tested recipes: Green Chile Salsa, Tomato Leather, Spiced Pear Butter, Eggplant Caviar, Blueberry Marmalade, Yellow Tomato Jam, Cranberry-Lime Curd, Preserved Lemons, Chicken Liver Pate, and more.
Keywords: Canning and preserving